The reality of using the System of the management E-Learning Classera Among Al-Andalus private Schools in the City of Sakaka from the point view of the Teachers - Al-Ruwaili, Arwa Abdullah Hulayyil; Al-Akloby, Saud Saad Fayez (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the reality of using the System of the management e-Learning Classera Among Al-Andalus private Schools in the city of Sakaka from the point view of the Teachers, and to identify the obstacles facing teachers when using the classera system, and to achieve the objectives of the study the descriptive approach was used, and the study tool was the questionnaire as a tool for data collection, and the study sample consisted of (32) teachers. The results of the study found that there are obstacles from the point of view of the teachers came with a degree of (medium) with an arithmetic average of (2.69 out of 5.00) The most impactful of these constraints, the weakness of the Internet, the high cost of the Internet. And that the reality of using the classera e-learning management system in Al-Andalus National Schools in Sakaka from the point of view of the teachers came with a (very high) degree with an arithmetic average of (4.68 out of 5.00).
Keywords: E- learning; Learning Management System; Classera